(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe a rapid and feasible perineal approach for the treatment of complete rectal prolapse. Subject and method: A case report detailing the surgical technique and procedure for treating complete rectal prolapse using a modified perineal stapled prolapse resection with linear staplers. An 82-year-old female patient presented with a one-year history of rectal bleeding and a prolapsing rectal mass during defecation. Results: The complete rectal prolapse was successfully resected transanally using two linear staplers. The procedure was completed in 30 minutes with minimal blood loss. The patient was discharged on the fourth postoperative day, and no recurrence was observed after one year of follow-up. Conclusion: The modified perineal stapled prolapse resection using linear staplers is a feasible and efficient technique for the treatment of complete rectal prolapse, offering advantages such as shorter operative time, less blood loss, and faster recovery compared to other perineal procedures.